FROM BALANCE TO DOMINANCE: THE INDO-PACIFIC POWER TRANSITION AND MAJOR POWERS’ RESPONSES - Manju Malik; Mamta Devi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Indo-Pacific region has emerged as a central focus of global geopolitics, characterized by its strategic significance and economic dynamism. The evolving global and regional geo-strategic landscape has shifted the international focus from the Euro-Atlantic region to the strategically crucial Indo-Pacific. The ascent of China, coupled with the United States’ efforts to maintain its primacy, has created a power transition that is reshaping the regional order. China's global ambitions hinge on establishing dominance in the Indo-Pacific region. In contrast, the United States is not seeking dominance but is committed to maintaining a stable and cooperative global order. China's aggressive behavior significantly elevates the risks of miscalculations and inevitable conflicts. This paper explores the transition from a balance of power to a dominance paradigm in the Indo-Pacific, focusing on the responses of major powers and the implications for regional and global stability. Furthermore, the paper analyzes the repercussions of this power transition, including security dilemmas, economic interdependence, and challenges to global governance.